Electron density in the solar corona from type III radio bursts - Batmunkh, Batbayar; Damdin, Batmunkh (Proceedings of the Mongolian Academy of Sciences, 2020)
It has been proven that electron density in the solar corona is determined by observing the frequency drift of type III radio bursts. We investigated the certain dependence of the scale height on the distance, which allows us to obtain different dependence of the frequency drift rate (FDR) on the frequency. The scale height is presented in a combination of two distance dependencies as H= αλT+(1-α)f(r). As a result of integration of equation, we obtain the electron density ne(r) in the form ne= n0(1+y)((-1) ⁄ ((1-α)b)), y=((1-α)/(α)) b ((r)/(λT) and the constants are determined in comparison with the empirical formulas for FDR. In particular, using the well-known empirical formula (dν)/(dt)=-0.01ν1.84, we can obtain (1-α)b=0.42. The obtained calculation results are compared with the results of other authors and they have been found to be consistent when choosing the parameters included in the formula. The calculation shows that this formula is in good agreement with the data at distances from the lower corona to the Earth's orbit. This dependence of electron density makes it possible to agree with the observed FDR as a function of frequency.